Tenaga Pendidik dan Literasi Digital: Tantangan Pembelajaran Di Era Industri 4.0 - Alfiyanto, Afif; Hidayati, Fitri (Institut Agama Islam Sumatera Barat Pariaman, 2022)
All education providers in learning in the Industrial Era 4.0 to immediately make changes. Previously, learning was limited by physical and conventional spaces, now, especially since the COVID-19 pandemic, learning on the network (online). Learning tools use gadgets, computers, the internet, and various applications that support bold learning. The hallmark of the start of the Industrial Era 4.0 is the use of new technologies that facilitate all work and streamline time in completing work. However, this situation cannot be found by educators. Many obstacles are experienced by educators in the learning process that utilizes simple to very sophisticated technology. Therefore, as an effort to help the difficulties and problems experienced by educators, educators must learn and recognize digital literacy well. This is because the source of information can be found, studied and practiced by educators in the learning process. But what is more important is implementing digital literacy in learning